On the formation of super-Jupiters: core accretion or gravitational instability? - Nguyen, Max; Adibekyan, Vardan (Astrophysics and space science, 2024)
The Core Accretion model is widely accepted as the primary mechanism for forming planets up to a few Jupiter masses. However, the formation of super-massive planets remains a subject of debate, as their formation via the Core Accretion model requires super-solar metallicities. Assuming stellar atmospheric abundances reflect the composition of protoplanetary disks, and that disk mass scales linearly with stellar mass, we calculated the total amount of metals in planet-building materials that could contribute to the formation of massive planets. In this work, we studied a sample of 172 Jupiter-mass planets and 93 planets with masses exceeding 4 M ♃ . Our results consistently demonstrate that planets with masses above 4 M ♃ form in disks with at least as much metal content as those hosting planets with masses between 1 and 4 M ♃ , often with slightly higher metallicity, typically exceeding that of the proto-solar disk. We interpret this as strong evidence that the formation of very massive Jupiters is feasible through Core Accretion and encourage planet formation modelers to test our observational conclusions.